Validation of the questionnaire "focus of attention for handball trainers in video analysis" - Óscar Gutiérrez Aguilar; Miguel Saavedra García; Juan J. Fernández Romero (Federación Extremeña de Balonmano; University of Extremadura, 2012)
The use of the Delphi method is indicated for the elaboration of questionnaires on a subject of study, which until now has little known information about it. Starting on an initial proposal, a group of 10 experts in handball made a series of modification proposals  until a final questionnaire was agreed of 34 items, with questions related with the four phases of the game that exist in handball. The questionnaire was given to 134 trainers from four different countries, verifying the validation of the questionnaire. The handball trainers gave most importance to the analysis with videos of the phases of play in attack and organized defense. Key words: handball, video analysis, tactic, Delphi.